The Effectiveness of using Google Drive in Digitizing Archives in the Accounting and Reporting Sub-Field of the Regional Financial and Asset Management Agency of Bali Province - Riadi, Kadek Argian Dwi; Widanti, Ni Putu Tirka; Wiadyani, Ida Ayu Putu Sri (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2024)
In the framework of the local government financial reporting process each year to BPK there are several components that are reported in the form of LRA, LO, Balance Sheet, LP SAL and CALK. In addition to these components, the Accounting and Reporting Sub Division also routinely reports periodic APBD realization reports (monthly, quarterly, semester and yearly), prepares annual financial reports, prepares materials for the preparation of Draft Regional Regulations on Accountability for Implementation of the APBD and Draft Governor Regulations on Explanation of APBD Accountability, and carries out other official duties assigned by superiors. The current condition that occurs in the Accounting and Reporting Subdivision is that the filing is not neat and the accumulation of physical archives is due to the archiving is still done manually, on the other hand, limited storage space results in the accumulation of files or documents that almost exceed storage capacity.